Risk and technological culture : towards a sociology of virulence - Loon, Joost van. (International library of sociology, 2002)
"The question as to whether we are now entering a risk society has become a key debate in contemporary social theory. Risk and Technological Culture presents a critical discussion of the main theories of risk - from Ulrich Beck's foundational work to that of his contemporaries such as Anthony Giddens and Scott Lash - and assesses the extent to which risk has impacted on modern societies. In this discussion Van Loon demonstrates how new technologies are transforming the character of risk and examines the relationship between technological culture and society through substantive chapters on topics such as waste, emerging viruses, communication technologies and urban disorders. In so doing this innovative new book extends the debate to encompass theorists such as Bruno Latour, Donna Haraway, Gilles Deleuze, Felix Guattari and Jean-Francois Lyotard."--Jacket.